KOMUNIKASI ETIKA BISNIS DALAM KEBERAGAMAN AGAMA DI KABUPATEN JEMBER - Nurul Widyawati Islami Rahayu; Khamdan Rifa’i; Abdul Rokhim (Indonesian Journal of Islamic Communication, 2021)
This study explores the communication business ethics of Sapto Darmo in Sukoreno Village, Umbulsari, Jember. These teachings rely on principles (honesty, autonomy, justice, mutual benefit and social integrity) and principles (unity, balance, free will and truth). The qualitative expert interview method was used to reveal this uniqueness. However, it turns out that this is still hampered by problems of lack of capital, the community's unpreparedness, the potential for business fraud and inadequate transportation.